Ekologi Integral dalam Tangan Warga: Ecobrick Furniture sebagai Refleksi Laudato Si’ di Padukuhan Keruk III - Wilhelmina Tjahyadi; Kristina Wulandari (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Padukuhan Dayakan II, located in Dayakan Village, Tanjungsari District, Gunung Kidul Regency, Yogyakarta, faces challenges in managing citizen data that is still done manually, causing slow administrative processes and vulnerability to errors. As a solution, students from Universitas Atma Jaya Yogyakarta (UAJY) developed an application based on Flutter and Dart for the digitalization of population data. This application development used the Agile methodology, which allows for iterative and flexible development according to user needs. The application facilitates the recording, updating, and searching of citizen data, reducing the time it previously took to search for one piece of data from 30 minutes to less than one minute. The application was tested through direct trials by village officials, and training was provided to the Kepala Dukuh (village head) as its partner to ensure the application could be used effectively. The results show that this application significantly improves administrative efficiency, accelerates public services, and enhances data accuracy. This application development is expected to be further developed with additional features to make administrative tasks easier and improve community services.